Constitution and jurisdiction - Ferrajoli, Luigi (2011)
A theoretical reflection on the nature and future of the entire system of guarantees in the face of the expansion of the scope of the jurisdiction as compared to the development of the system of legal limits and obligations granted to the public power structures. For every expansion in legality an expansion in jurisdiction should follow and hence, a growth of judicial power which, at the same time, requires the reinforcement of its legitimacy. Thus, the expression of the jurisdiction in line with the expansion of the legality established by the Constitution, allows us to rethink the sources for the legitimization of the Judiciary and its separation from the other public powers. The referred expansion process is not exhausted and expresses a clear tendency towards its ulterior development; a growth that evidences that the guarantees and the role of the jurisdiction are presently insufficient in relation to the function for the protection of rights stipulated in the different statal and suprastatal constitutions, thereby entailing the need to rethink the role of the jurisdiction, in the theoretical plane as well.